2015
DOI: 10.1208/s12248-015-9762-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and Fit-for-Purpose Validation of a Soluble Human Programmed Death-1 Protein Assay

Abstract: Abstract. Programmed death-1 (PD-1) protein is a co-inhibitory receptor which negatively regulates immune cell activation and permits tumors to evade normal immune defense. Anti-PD-1 antibodies have been shown to restore immune cell activation and effector function-an exciting breakthrough in cancer immunotherapy. Recent reports have documented a soluble form of PD-1 (sPD-1) in the circulation of normal and disease state individuals. A clinical assay to quantify sPD-1 would contribute to the understanding of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…PD‐1/PD‐L1/PD‐L2 exist in the peripheral blood in soluble forms 20,21 . Soluble PD‐1 (sPD‐1) originates from an alternative splice variant of the PD‐1 gene, whereas soluble PD‐L1 (sPD‐L1) and soluble PD‐L2 (sPD‐L2) are assumed to originate from proteolytic cleavage of membrane PD‐L1/PD‐L2 22‐25 .…”
Section: Introductionmentioning
confidence: 99%
“…PD‐1/PD‐L1/PD‐L2 exist in the peripheral blood in soluble forms 20,21 . Soluble PD‐1 (sPD‐1) originates from an alternative splice variant of the PD‐1 gene, whereas soluble PD‐L1 (sPD‐L1) and soluble PD‐L2 (sPD‐L2) are assumed to originate from proteolytic cleavage of membrane PD‐L1/PD‐L2 22‐25 .…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 is expressed on tumor-infiltrating lymphocytes and its soluble form is measured in several cancers (Ni et al 2015 ; Rijnders et al 2017 ). We demonstrated that serum PD-1 levels increased in advanced RCC patients, when measured by Nivolumab-based ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Both monomeric sPD-1-His and dimeric sPD-1-Fc were available as recombinant calibrator material. During the development of a sPD-1 electrochemiluminescent (ECL) assay (22), surface plasmon resonance studies showed the capture antibody had a higher binding affinity for sPD-1-Fc than sPD-1-His (0.5 versus 2.8 nM). Consequently, there was approximately a 50-fold difference in concentration-dependent signal when the calibrator curves of both sPD-1-His monomer and sPD-1-Fc dimer were tested (Fig.…”
Section: Case Study 1: Differences In the Physiochemical Structure Ofmentioning
confidence: 99%